2010
DOI: 10.1007/s11661-010-0232-4
|View full text |Cite
|
Sign up to set email alerts
|

Criteria of Grain Refinement Induced by Ultrasonic Melt Treatment of Aluminum Alloys Containing Zr and Ti

Abstract: It is well known that ultrasonic melt treatment (UST) promotes grain refinement in aluminum alloys. Cavitation-aided grain refinement has been studied for many years; however, it is still not being applied commercially. The current article summarizes the results of experimental work performed on various alloying systems at different stages of solidification. The influence of UST parameters and solidification conditions on the final grain structure is analyzed. It was found that small additions of zirconium and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
177
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 237 publications
(187 citation statements)
references
References 20 publications
9
177
1
Order By: Relevance
“…It has been suggested and demonstrated that ultrasonic treatment results in fragmentation of primary intermetallics, increasing their number [8][9][10]. In order to analyze the effect of ultrasonic treatment on formation of Al 3 Ti and related grain refinement in a hyperperitectic Al-Ti alloy, the Al-0.4 wt% Ti alloy was subjected to UST in the solidification range of Al 3 Ti, from 720 to 680°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested and demonstrated that ultrasonic treatment results in fragmentation of primary intermetallics, increasing their number [8][9][10]. In order to analyze the effect of ultrasonic treatment on formation of Al 3 Ti and related grain refinement in a hyperperitectic Al-Ti alloy, the Al-0.4 wt% Ti alloy was subjected to UST in the solidification range of Al 3 Ti, from 720 to 680°C.…”
Section: Resultsmentioning
confidence: 99%
“…Aluminum grain refinement occurs when the UST is performed in the temperature range of primary solidification of Al 3 (Zr, Ti) [9]. The suggested mechanisms include the heterogeneous nucleation of (Al) on smaller intermetallic particles at higher undercooling [10].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Although ultrasound-induced grain refinement has been shown effective in many metallic alloy systems, almost all previous research have interpreted the mechanism of grain refinement based on post-mortem microstructural characterization of the solidified alloys and empirical correlation, if any, between the measured grain size and the input ultrasonic power. [4,5] A very recent high-speed imaging study of ultrasonic treatment of a solidifying organic transparent alloy revealed that the shock wave emitted from imploding bubbles can fracture the growing dendrites, [6] increasing the grain multiplication effect that leads to the enhancement of grain refinement. However, in situ and real time studies of the fundamentals of how the highly dynamic ultrasonic waves and the ultrasonic bubbles interact with the liquid metal, the semisolid and solid phases nucleated during solidification have not been reported mainly due to the difficulties in studying the bubble dynamics in the opaque liquid metal.…”
Section: Applying Ultrasonic Waves Inside Liquid Mediamentioning
confidence: 99%
“…Their results indicated that the wetted side of an oxide film can act as nucleation sites for the Fe-bearing intermetallics. More recently, Atamanenko et al [18] investigated the grain refining effect of exogenous oxides combined with ultrasonic treatment in pure Al (99.95%Al), and attributed the grain refinement to cavitation-induced heterogeneous nucleation through the activation of oxides. In addition, it has been demonstrated that, via the introduction of intensive melt shearing using the MCAST process, naturally occurring oxides in liquid Mg-and Al-alloys can be harnessed to enhance heterogeneous nucleation for microstructural refinement in Mg and Al alloys [19][20][21].…”
Section: Introductionmentioning
confidence: 99%